Does reproductive mode affect sexually-selected coloration? Evaluating UV–blue spots in parthenogenetic and bisexual lizards of the genus Darevskia. Issue 2 (17th July 2020) - Abramjan, Andran; Arakelyan, Marine; Frynta, Daniel
Abstract: Sexual selection often leads to evolution of conspicuous signals, raising the chances of attracting not only potential mates, but also predators. In lacertid lizards, ultraviolet (UV)–blue spots on flanks and shoulders represent such a trait. Some level of correlation between male and female ornamentation is also known to exist. Therefore, the phenotype of females may change in the absence of sexual selection. We tested this hypothesis on a complex of parthenogenetic and bisexual lizards of the genus Darevskia . We evaluated area, counts, and chromatic properties (UV opponency, saturation) of UV–blue spots and compared the values between the clones and their bisexual progenitor species. We found a fair heterogeneity between the parthenogenetic species, but no general tendency toward higher crypsis or conspicuousness. Values of the parthenogens were not significantly different from the values of sexual females. A possible explanation is that the changes in selective forces associated with parthenogenetic reproduction are too small to affect the resulting pattern of selective pressures on the studied traits, or that the phenotypes of the parthenogens result from the unique combination of parental genomes and are conserved by clonal reproduction.